PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA, BUDAYA PERUSAHAAN DAN KOMPENSASI TERHADAP LOYALITAS PEGAWAI PT ANGKASA PURA 1 KANTOR CABANG BANDAR UDARA ADI SOEMARMO - Rahmadini Intan Nurrohmah; Rusnandari Retno Cahyani; Annisa Indah Mutiasari (Journal Of Business, Finance, and Economics (JBFE), 2024)
This research is entitled the influence of leadership style, work environment, corporate culture and compensation on employee loyalty of PT Angkasa Pura 1 Adi Soemarmo Airport Branch Office. This research is a descriptive study using a quantitative approach. The population in this study were employees of PT Angkasa Pura 1 Adi Soemarmo Airport Branch Office, the sample used was 104 respondents. The sampling technique in this study used saturated sampling technique, where all members of the population were used as samples. Based on data analysis conducted by researchers, it states that the variables of leadership style (X1), work environment (X2), corporate culture (X3) and compensation (X4) simultaneously have a positive and significant effect on employee loyalty. However, partially only corporate culture (X3) and compensation (X4) have a positive and significant effect on employee loyalty.